Pengaruh Kepercayaan, Service Quality Dan Web Quality Terhadap Loyalitas Konsumen dengan Kepuasan Sebagai Variabel Intervening - Ningrum, Panca Cahya; Prabowo, Heri; Indrisari, Ika (Universitas Pahlawan Tuanku Tambusai, 2024)
This research is based on the decline in users from Tokopedia e-commerce application. In 2022 Tokopedia will be in first place in Indonesia's Top E-Commerce with 158 million users. In 2023 it will drop to 2nd place with 131 million users. The lack of loyalty on Tokopedia showed by decline of the users that use Tokopedia. This research uses a quantitative approach to examine variables related to consumer loyalty. The instrument used to obtain primary data was a questionnaire distributed online using G-Form. In this research, it was found that trust can influence consumer loyalty. Meanwhile, service quality and web quality do not affect consumer loyalty. The intervening variable satisfaction can influence consumer loyalty. After going through satisfaction, trust, service quality and web quality can give an effect to loyalty.